Stroke screening and health-related physical fitness testing in medical staff members in Urumqi, China - Yu-Shan Wang (KeAi Communications Co., Ltd., 2017)
Objective: Stroke is the leading cause of death and disability, and is closely related to a lack of exercise. Currently, most Chinese medical staff members lack exercise and may be at risk for stroke. We sought to determine the risk factors for stroke and study the significance of health-related physical fitness testing in stroke prevention among Chinese medical staff members. Methods: A total of 627 subjects from Urumqi, Xinjiang, China, were included in the study and a survey was conducted from 1st January 2016 to 1st February 2016. Stroke screening and health-related physical fitness testing were completed according to the standard protocol, and the related data were analyzed. Results: Based on the screening, 27.6% (n = 173) of the subjects were at high risk for stroke. The top risk factors for stroke in these subjects were dyslipidemia, lack of exercise or mild physical activity, being overweight or obese, and high blood pressure. Body weight, body mass index, body fat, visceral fat area, body fat percentage, and basal metabolic rate were significantly higher (P < 0.01) in subjects at high risk for stroke than in subjects who were not at high risk. Lung capacity, step index, grip test, vertical jump, and sit-up/push-up index were significantly lower (P < 0.01) in subjects at high risk for stroke than in subjects who were not at high risk. Conclusions: A large proportion of China's on-the-job medical personnel is at high risk for stroke. This may be related to the nature of the profession and warrants more attention from the society. The health-related physical fitness measurement parameters in subjects at high risk for stroke were significantly different from those in subjects who were not at high risk. Screening and health-related physical fitness testing in medical staff members may contribute to stroke prevention. More rigorous controlled clinical trials will be needed in the future. Keywords: Stroke, High risk population, Health-related physical fitness, Prevention